2019
DOI: 10.1111/1467-8489.12359
|View full text |Cite
|
Sign up to set email alerts
|

Climate change adaptation actions by fish farmers: evidence from the Niger Delta Region of Nigeria

Abstract: This paper examined climate change adaptation strategies in fish farming and the effect of such methods on the profit of fish farmers in the Niger Delta region of Nigeria, Africa’s most populous country. Using cross‐sectional data obtained from 420 fish farmers from the region and applying multivariate probit and instrumental variable regressions, the study found that fish farmers have adopted a broad range of strategies to address climate risk and that these have significantly increased farmers’ profit. Our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 53 publications
1
15
0
4
Order By: Relevance
“…It is interesting to note that 71%, 91% and 80% of the farmers had television, mobile phone and radio, respectively. These assets enhance both reception and communication of climate information, which help the farmers in overcoming adverse effects of climate change on agricultural production [45]. Similarly, 19 percent had at least a car, 67 percent had at least a motorcycle, 8 percent had at least a tricycle and 42 percent owned at least one bicycle.…”
Section: Socio-economic Characteristics Of the Farmersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that 71%, 91% and 80% of the farmers had television, mobile phone and radio, respectively. These assets enhance both reception and communication of climate information, which help the farmers in overcoming adverse effects of climate change on agricultural production [45]. Similarly, 19 percent had at least a car, 67 percent had at least a motorcycle, 8 percent had at least a tricycle and 42 percent owned at least one bicycle.…”
Section: Socio-economic Characteristics Of the Farmersmentioning
confidence: 99%
“…Efficient water management and intermittent draining of paddy rice fields are very important strategies for reducing and avoiding methane emissions. Insurance with a score of 0.711 indicated that insurance is a vital adaptation strategy which covers the farmer during periods of total agricultural failure occasioned by climate change [45]. Reliance on climate information and forecasts is another important climate-smart agricultural strategy that assists farmers with current information on climate change.…”
Section: Climate-smart Agricultural Practices/technologies In Rice Productionmentioning
confidence: 99%
“…The South-East has five (5) E longitude. The land mass of the zone measure about 11 million hectares, and has a population of about 16 million [12]. The climatic condition of the zone is that of atropical rainforest and favors agriculture.…”
Section: Study Areamentioning
confidence: 99%
“…Nigeria is one of the countries located within the sub-Saharan African region, with a growing population of over 200 million people [12]. The country is geopolitically divided into six zones, and the South-East includes a teeming population of over 20 million people [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation